Cavitation and erosion effects on hydraulic performances of a submersible drainage pump - Md Rakibuzzaman; Sang-Ho Suh; Hyoung-Ho Kim; Md. Didarul Islam; Ling Zhou; Mahmoud A. El-Emam (Alexandria Engineering Journal)
Hydraulic performance and operational stability of submersible drainage pumps can be affected by cavitation and erosion when used for draining water from buildings. A parametric study is essential to improve the suction performance and accurately identify the cavitation and erosion phenomena in the pump, providing a technical reference for monitoring its optimal operation. Therefore, the main objective of this research is to develop an energy-saving, high-efficiency submersible pump capable of emergency response. In this paper, the Reynolds-average Navier-Stokes (RANS) equations were applied to the steady calculation of the submersible pump, which was discretized by the finite volume method. The Reyleigh-Plesset cavitation model was considered for interphase mass transfer to predict and find the cavitation characteristics. Additionally, the discrete phase model (DPM) was adopted as an Eulerian-Eulerian approach combined with Grant and Tabakoff's erosion model to capture the erosion effects in the pump numerically. A test pump was installed, and an experiment was conducted to assess hydraulic performance, validated with computational data. Improving the impeller or casing shape can increase NPSH3 % by at least 3.80 %, with a potential improvement of 4.083 % when only the impeller shape is changed. Erosion rate density increases with particle inflow rate, but model differences decrease as the flow rate increases. Modifying the impeller and casing shapes can reduce the average erosion rate density by at least 25 %. Average efficiency improvements of 4–5 % can be achieved by optimizing the casing shape, though practical implementation is challenging. Optimizing the pump's flow path is essential for improving hydraulic performance and reducing erosion and cavitation.